Canadian industrial policy - Morici, Peter; Smith, Arthur James Ralph; Lea, Sperry (Washington, D.C. : National Planning Association, 1982)
The purpose of this study is to examine the motivations behind, contents of and outlook for Canadian industrial policy and to explore some of its potential consequences for the United States and U.S.-Canadian economic relations.
"June 1982."
Includes bibliographical references.
ne 11/06/2018
Loans
Keywords: Industrial policy